2020
DOI: 10.22434/ifamr2019.0121
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Internet of Things depends on intention: young farmers’ willingness to accept innovative technology

Abstract: Innovative applications of smart technology constitute a current trend in agricultural development. This study employed a technology acceptance model to explore the intention of young farmers to apply Internet of Things systems in field-level management of Taiwanese farms. An online questionnaire was used to collect data regarding farmers aged 45 years or younger who were currently engaged in agricultural production. Statistical analysis of 241 valid questionnaires revealed that young farmers’ intention to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…These findings indicate that larger farm size or volume of business may enhance farmers' investments in SA technologies. This finding accords with those of previous studies [13,25,26] that reported a positive relationship between farm size or revenue and innovation adoption. Most sociodemographic characteristics were not significantly associated with SA adoption, except age, which was positively correlated with SA adoption.…”
Section: Effects Of Sa Knowledge and Importance On Sa Adoptionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings indicate that larger farm size or volume of business may enhance farmers' investments in SA technologies. This finding accords with those of previous studies [13,25,26] that reported a positive relationship between farm size or revenue and innovation adoption. Most sociodemographic characteristics were not significantly associated with SA adoption, except age, which was positively correlated with SA adoption.…”
Section: Effects Of Sa Knowledge and Importance On Sa Adoptionsupporting
confidence: 93%
“…These emerging concepts have slight differences in terms of the emphasis on specific technological applications. Most of these concepts share common traits and values in incorporating new and intelligent technologies into farming practices and introducing resource use efficiency approaches that minimize production costs, reduce farming risks, and increase productivity [ 13 ]. The inventory of the European smart agricultural knowledge and innovation systems (Smart-AKIS) program indicates that SA is mainly related to three interconnectable new technology categories: farm management information systems, precision farming, and agricultural automation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The WTP is also the market demand curve for that commodity. This approach has been effectively applied and adopted in the previous studies related to different fields of study with especially in rural and farming activities (Asrat, Belay and Hamito, 2004;Othman et al, 2009;Energyplus, 2011;Divilly, 2018;Etsay, Negash and Aregay, 2019;Haile, 2019, 2020;Chuang, Wang and Liang, 2020;Kansanga et al, 2020;ÖZSAYIN, 2020).…”
Section: Model Of Willingness To Paymentioning
confidence: 99%